The Effect of Benzyl Isothiocyanate on the Expression of Genes Encoding NADH Oxidase and Fibronectin-Binding Protein in Oral Streptococcal Biofilms - Alhandal, Hawraa; Almesaileikh, Esraa; Bhardwaj, Radhika G.; Al Khabbaz, Areej; Karched, Maribasappa (Frontiers in Oral Health, 2022)
Recent studies have shown that antimicrobial treatment results in up- or down regulation of several virulence-associated genes in bacterial biofilms. The genes encoding NADH oxidase (nox) and fibronectin-binding protein (fbp) are known to play important roles in biofilm growth of some oral bacterial species. The objective was to study the effect of benzyl isothiocyanate (BITC), an antimicrobial agent from Miswak plant, on the expression of nox and fbp genes in some oral streptococci. The biofilms were treated with BITC and mRNA expression of nox and fbp genes was measured by comparative ∆∆Ct method. The highest amount of biofilm mass was produced by A. defectiva, followed by S. gordonii, S. mutans, G. elegans and G. adiacens. Upon treatment with BITC, S. gordonii biofilms showed highest folds change in mRNA expression for both fbp and nox genes followed by S. mutans, A. defectiva, and G. adiacens. G. elegans mRNA levels for nox were extremely low. In conclusion, BITC treatment of the biofilms caused an upregulation of biofilm-associated genes fbp and nox genes in most of the tested species suggesting the significance of these genes in biofilm lifestyle of these oral bacteria and needs further investigation to understand if it contributes to antimicrobial resistance.